Anmeldelser - Mauritsen, Anne Lundahl; Poulsen, Frederik; Borup, Jørn (Religionsvidenskabeligt Tidsskrift, 2021)
Annmeldelser til RvT 71: Erika Wallander: Unity, Division and the Religious Mainstream in Sweden (Anne Lundahl Mauritsen) Tero Alstola: Judeans in Babylonia: A Study of Deportees in the Sixth and Fifth Centuries BCE (Frederik Poulsen) Iselin Frydenlund & Michael Jerryson: Buddhist-Muslim Relations in a Theravada World (Jørn Borup)